Obtenção de compositos nanoestruturados de PSU/Ferrocarbonila a partir do processo de eletrofiação - Gil, Daniel Molina [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Nanostructured materials have been studied and developed increasingly to be applied in the aerospace sector.. Among the various processes available with great growth potential for obtaining nanostructured composites, stands out electrospinning, which has the advantage of obtaining nanometric sizes fibers, increasing significantly, various properties such as mechanical strength; flexibility of functionality of areas (which in another words can be described as the synthesis of another polymer upon electrospinning material, or the possible addition of functional groups to the electrospinning material) and aspect ratio (length /diameter). This is a process where blankets are produced consisting of nanofibres from the application of an electric field in the polymer solution, allowing to obtain a wide range of materials with various applications, and can even be used as the absorbing material of electromagnetic radiation. The materials known as MARE (Electromagnetic Radiation Absorbing Material) are named in this way because it have properties that allow them to exchange energy of the incident electromagnetic radiation by heat energy. Thus, this graduate work aims to study the influence of processing parameters through electrospinning (concentration, working distance and voltage) combined with a ferromagnetic additive in the production of nanofibers in order to be apply as absorbing materials of electromagnetic radiation (RAW). The blankets were produced by electrospinning using as solution N-Ndimetil-acetamina (PSU / DMAc), and this same solution with ferrocarbonila. The blankets were characterized by thermal behavior (DSC and TGA), morphology (RAW), rheology, electric resistivity and reflectivity, being the last parameter analyzed in the microwave range between 1-30 GHz. The processing parameters that influence the final result of the ...(Complete abstrac click electonic access below)

Materiais nanoestruturados vêm sendo estudados e desenvolvidos cada vez mais para serem aplicados no setor aeroespacial. Dentre os diversos processos disponíveis com grande potencial de crescimento para a obtenção de compósitos nanoestruturados, destaca-se a eletrofiação, pois este tem a vantagem de obter fibras de tamanhos nanométricos, aumentando, de forma significativa, diversas propriedades tais como: resistência mecânica; flexibilidade da funcionalidade das superfícies (que em outras palavras pode ser descrito como a síntese de outro polímero em cima do material eletrofiado, ou ainda a possível adição de grupos funcionais ao material eletrofiado) e razão de aspecto (comprimento/diâmetro). Este consiste em um processo onde são produzidas mantas constituídas por nanofibras a partir da aplicação de um campo elétrico na solução polimérica, permitindo a obtenção de uma grande variedade de materiais, com diversas aplicações, podendo até mesmo ser utilizado como material absorvedor de radiação eletromagnética. Os materiais conhecidos como MARE (Material Absorvedor de Radiação Eletromagnética) são assim chamados por possuírem propriedades que lhes permitem a troca de energia da radiação eletromagnética incidente pela energia térmica. Desta forma, este trabalho de graduação visa estudar a influência dos parâmetros de processamento via eletrofiação (concentração, distância de trabalho e tensão) combinados com um aditivo ferromagnético, na produção de nanofibras para aplicação como materiais absorvedores de radiação eletromagnética (MARE). As mantas foram produzidas por eletrofiação utilizando como solução o N-Ndimetil-acetamina (PSU/DMAc), e esta mesma solução com ferrocarbonila. As mantas foram caracterizadas quanto ao comportamento térmico (DSC e TGA), morfologia (MEV), ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Eletrofiação; Materiais nanoestruturados; Ferro; Electrospinning